Percepções de profissionais da atenção primária em saúde em relação à infraestrutura, atitudes e conhecimentos para o manejo das Doenças Crônicas não Transmissíveis - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
Chronic Noncommunicable Diseases (NCDs) are characterized by having an uncertain etiology, multiple risk factors, which may be associated with physiological deficiencies and disabilities. Some people with these conditions can maintain an active and healthy lifestyle, as long as they receive health care and attention from a technically trained and up-to-date team. The main objective of the present study was to analyze the level of technical knowledge about NCDs, physical, personnel and logistical perceptions regarding their work, attitudinal self-assessment and stress level of health professionals in Primary Health Care (PHC) in Ponta Grossa that work to combat NCDs and associated factors. The methodology used for this research was a cross-sectional, exploratory and quantitative study with qualitative variables and occurred in two stages. The first stage consisted of surveying the number of professionals working in the selected Basic Health Units - UBS and applying a diagnostic assessment questionnaire to the professionals, where it was possible to characterize and obtain their perceptions on the topics covered in the questionnaire; and the second stage was characterized by the tabulation and analysis of the collected data. 36 health professionals participated in the research, of which only 47.22% had completed training in NCDs in the last five years. No statistically significant difference was observed between responses in all categories. When analyzing the participants' stress level, the score suggests a moderate level. Perceptions regarding knowledge on NCDs reflect the need to strengthen prevention and treatment strategies, and to improve support for professionals' working conditions, to guarantee comprehensive and effective health care for the community served. The results found indicate that strengthening professionals through technical training can have a great influence on the treatment of users. This study shows the importance and relevance of an intervention model based on continuing health education, which, if reproduced in the public health network, can have a significant social impact.
Keywords: Atenção Primária à Saúde; Educação em Saúde; Doenças crônicas não transmissíveis; Obesidade; Primary Health Care; Health Education; Chronic non-communicable diseases; Obesity; CNPQ::CIENCIAS DA SAUDE